Synthetic PAMPS gel activates BMP/Smad signaling pathway in ATDC5 cells, which plays a significant role in the gel‐induced chondrogenic differentiation. Issue 3 (27th November 2015) - Goto, Keiko; Kimura, Taichi; Kitamura, Nobuto; Semba, Shingo; Ohmiya, Yoshihiro; Aburatani, Sachiyo; Matsukura, Satoko; Tsuda, Masumi; Kurokawa, Takayuki; Ping Gong, Jian; Tanaka, Shinya; Yasuda, Kazunori
Abstract: The purposes of this study were to identify signaling pathways that were specifically activated in ATDC5 cells cultured on poly (2‐acrylamido‐2‐methylpropanesulfonic acid) (PAMPS) gel in insulin‐free maintenance medium and to evaluate the significance of the determined signaling pathways in the chondrogenic differentiation induced by this gel. In this study, ATDC5 cells cultured on PAMPS gel using the maintenance medium without insulin (PAMPS Culture) were compared with cells cultured on polystyrene using the differentiation medium containing insulin (PS‐I Culture). The microarray analysis, Western blot analysis, and real‐time PCR analysis demonstrated that the TGF‐β/BMP signaling pathway was significantly enhanced at Days 1, 2, and 3 in the PAMPS Culture when compared with the PS‐I Culture. Inhibition of the BMP type‐I receptor reduced the phosphorylation level of Smad1/5 and expression of type‐2 collagen and aggrecan mRNA in the cells accompanied by a reduction in cell aggregation at Day 13 in the PAMPS Culture. The inhibition of the TGF‐β/BMP signaling pathway significantly inhibited the chondrogenic differentiation induced by the PAMPS gel. The present study demonstrated that synthetic PAMPS gel activates the TGF‐β/BMP/Smad signaling pathway in the ATDC5 cells in the absence of insulin, and that this activation plays a significant role in the chondrogenic differentiation induced by PAMPS gel. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 734–746, 2016.